RELIGIOUS READING MATERIALS AND RELIGIOUS ORIENTATION OF HIGH SCHOOL ISLAMIC EDUCATION TEACHERS IN BANDAR LAMPUNG - Nur, Mahmudah; Noorbani, Muhammad Agus (Balai Penelitian dan Pengembangan Agama Semarang, 2019)
This paper aims at showing the result of the research on the variety of religious reading materials and religious orientation based on religious reading materials of Islamic Education (Pendidikan Agama Islam/PAI) teachers in Bandar Lampung. Religious reading materials is one of the sources of knowledge being read by Islamic Education teachers as an effort to improve the quality of their knowledge. Utilizing mixed methods with psychology of religion approach and discourse analysis, this study aims to know the variety that PAI high school teachers in Bandar Lampung for the enrichment of teaching contents at schools and to find the linkages between religious reading materials with the religious orientation of PAI teachers in Bandar Lampung. The findings of this research show that the orientation of PAI high school teachers in Bandar Lampung was more categorized as intrinsic and a few was categorized as extrinsic. Based on the religious reading materials of PAI high school teachers in Bandar Lampung, the teachers who are categorized as intrinsic are more varied in terms of topics and authors compared to the teachers who are categorized as extrinsic.